2007
DOI: 10.1111/j.1600-0501.2007.01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone healing dynamics at buccal peri‐implant sites

Abstract: When implants are placed into extraction sites, proximity to the buccal alveolar crest appears a major consideration. The observations herein suggest that the width of the buccal alveolar ridge should be at least 2 mm to maintain the alveolar bone level. These observations likely have general implications for implant placement using most surgical protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
109
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 20 publications
9
109
0
3
Order By: Relevance
“…Post-extraction resorption of the buccal wall was recognized as inevitable in cases of the immediate placement of implants [6782526]. Our results confirmed, in control sites, that immediate implant placement did not avoid post-extraction resorption, regardless of the alveolar bone height, which is in agreement with the current literature [6782021]. At 3 months, dimensional changes of the socket were most pronounced on the buccal side, and greater in magnitude than has been reported in other studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Post-extraction resorption of the buccal wall was recognized as inevitable in cases of the immediate placement of implants [6782526]. Our results confirmed, in control sites, that immediate implant placement did not avoid post-extraction resorption, regardless of the alveolar bone height, which is in agreement with the current literature [6782021]. At 3 months, dimensional changes of the socket were most pronounced on the buccal side, and greater in magnitude than has been reported in other studies.…”
Section: Discussionsupporting
confidence: 91%
“…A study showed that the buccal wall must have an original width of 2 mm to avoid loss of bone height. In addition to the importance of the thickness of the alveolar buccal wall, the space between the implant and socket is also involved in the phenomenon of bone reduction [21]. Indeed, the diameter of a dental root is often larger than the implant.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of facial bone architecture has been related to a facial bone wall thickness of 2 mm in an experimental dog study (Qahash et al, 2008). In the anterior maxilla, the facial bone wall is usually thinner than 2 mm, as demonstrated in several CBCT studies (Braut et al, 2011;Januario et al, 2011;Vera et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Since placing IMIs does not eliminate post-extraction alveolar ridge remodeling [37,38], it is recommended that IMIs be submerged by up to 2 mm on the buccal aspect to compensate for the expected buccal crestal bone loss [29,33,39]. This is particularly important if the thickness of the buccal wall is <2 mm [40,41]. Huang, et al [42] compared implants placed at the level of the bone crest to those submerged by 1.5 mm in dogs, and found the latter to have better crestal bone preservation in relation to the implant neck after 4 months in function.…”
Section: Managing Socket Anatomymentioning
confidence: 99%